Enabling Lithium Metal Anode in Nonflammable Phosphate Electrolyte with Electrochemically Induced Chemical Reactions. Issue 35 (9th June 2021) - Zhang, Haochuan; Luo, Jingru; Qi, Miao; Lin, Shiru; Dong, Qi; Li, Haoyi; Dulock, Nicholas; Povinelli, Christopher; Wong, Nicholas; Fan, Wei; Bao, Junwei Lucas; Wang, Dunwei
Abstract: Lithium metal anode holds great promises for next‐generation battery technologies but is notoriously difficult to work with. The key to solving this challenge is believed to lie in the ability of forming stable solid‐electrolyte interphase (SEI) layers. To further address potential safety issues, it is critical to achieve this goal in nonflammable electrolytes. Building upon previous successes in forming stable SEI in conventional carbonate‐based electrolytes, here we report that reversible Li stripping/plating could be realized in triethyl phosphate (TEP), a known flame retardant. The critical enabling factor of our approach was the introduction of oxygen, which upon electrochemical reduction induces the initial decomposition of TEP and produces Li3 PO4 and poly‐phosphates. Importantly, the reaction was self‐limiting, and the resulting material regulated Li plating by limiting dendrite formation. In effect, we obtained a functional SEI on Li metal in a nonflammable electrolyte. When tested in a symmetric Li∥Li cell, more than 300 cycles of stripping/plating were measured at a current density of 0.5 mA cm −2 . Prototypical Li‐O2 and Li‐ion batteries were also fabricated and tested to further support the effectiveness of this strategy. The mechanism by which the SEI forms was studied by density functional theory (DFT), and the predictions were corroborated by the successful detection of the intermediates and products. Abstract : A critical challenge toward realizing Li metal anode has been the lack of stable SEI between Li and the electrolyte. We report an approach of using oxygen to induce unique decompositions of organic phosphate solvent, where simple reactions favor the formation of a stable SEI. This method permits repeated Li stripping/plating on Li metal in a flame retardant electrolyte. The results promise safe operations of Li in next generation batteries.